2010
DOI: 10.3923/pjbs.2010.546.550
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Medium to Increase the Production of Desferrioxamine B (Desferal) in Streptomyces pilosus

Abstract: The aim of this study was optimization of culture medium in direction of increasing the production rate of desferrioxamine B. Streptomycetes are the most widely studied and well known genus of the actinomycete family. Streptomycetes usually inhabit soil and are important decomposers. The genus Streptomyces are Gram-positive and GC rich bacteria that are important for production of many antibiotics and secondary metabolites. These metabolites are important in industrial and medical fields. Deferoxamines (also k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…There is a plethora of evidence that the types of carbon sources and nitrogen sources as well as other culture media supplements (salts and precursors) greatly influence secondary metabolite biosyntheses, e.g., siderophore [21,[25][26][27]. In good accordance with this, different combinations of carbon sources, nitrogen sources, and MOPS resulted in various DFO-E yields during the production of this hexadentate cyclic siderophore by S. parvulus.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…There is a plethora of evidence that the types of carbon sources and nitrogen sources as well as other culture media supplements (salts and precursors) greatly influence secondary metabolite biosyntheses, e.g., siderophore [21,[25][26][27]. In good accordance with this, different combinations of carbon sources, nitrogen sources, and MOPS resulted in various DFO-E yields during the production of this hexadentate cyclic siderophore by S. parvulus.…”
Section: Discussionmentioning
confidence: 76%
“…Todokoro et al [19] demonstrated that ferrichrysin production by A. oryzae can even reach 2.8 g/l. Furthermore, Mortazavi and Akbarzadeh [32] reported on almost 2 g/l DFO-B yields with S. pilosus ATCC 19797, and Chiani et al [27] Not surprisingly, although production data for DFO-B [27,32,33] are abundant because this siderophore is widely used for the treatment of iron overload in humans, similar data for the optimization of DFO-E production are scarcely available [21,22]. Nevertheless, the highest DFO-E yield was reported by Meiwes et al [22], which reached 12 g/l in a fed-batch fermentation system with Streptomyces olivaceus TÜ 2718.…”
Section: Discussionmentioning
confidence: 98%
“…Automated secondary metabolism analysis using antiSMASH 4.0.2 (12) predicted 25 biosynthesis gene clusters (BGCs). Eight of these matched known clusters for the biosynthesis of desferrioxamine B (13, 14), sioxanthin (15), and landomycin (16). The remaining clusters were predicted to encode 2 terpenoid-, 4 nonribosomal peptide synthetase (NRPS)-, 9 polyketide synthase (PKS)-, 1 hybrid-NRPS-PKS-, and 6 ribosomally synthesized and posttranslationally modified peptide (RiPP)-based compounds.…”
Section: Announcementmentioning
confidence: 91%
“…Interestingly, one of the most notable iron chelators desferrioxamine is of natural origin. Desferrioxamine is produced by the Streptomyces species [46], with a molecular structure that consists of multiple hydroxyl and carbonyl groups that can chelate iron in a 1 : 1 ratio. Its relevance in iron overload management lies in its specific preference in the binding of iron over calcium to protect myocytes against peroxide-induced damage [47].…”
Section: Dietary Sources Of Iron-chelatorsmentioning
confidence: 99%